MAKING ITS OWN ENEMY: ANALISIS DILEMA KEAMANAN DALAM KOMPETISI RUANG ANGKASA AMERIKA SERIKAT-CINA - ezraputi salsabila; Hermini Susiatiningsih; Muhammad Faizal Alfian (Journal of International Relations Diponegoro, 2022)
Technology has been present and has become an essential part of every human activity. The magnitude of the involvement of technology creates dependency and encourages countries to make technology one of the critical elements of the state. Today, most modern services rely on space-based technology to operate, which makes space an essential domain for the country. Although the United States still dominates space, China's emergence as a new power is causing concern for the United States. The accumulation of power as proof of state competency took place between these two countries. This article uses a literature study method where the data source is obtained from primary and secondary data. The result of this study is to present evidence that the United States' fear of China's rise in space is the result of US policy itself. This paper highlights three key moments that show how US policy has contributed significantly to the rise of its rival, namely China.